Development of a bone-targeted pH-sensitive liposomal formulation containing doxorubicin: physicochemical characterization, cytotoxicity, and biodistribution evaluation in a mouse model of bone metastasis - Mônica Cristina Oliveira; Diêgo S. Ferreira; Samilla Faria; Sávia Caldeira de Araújo Lopes; Cláudia Teixeira; Ângelo Malachias; Rogério Magalhães-Paniago; José Dias de Souza Filho; Bruno L. Oliveira; Alexander R. Guimarães; Peter Caravan; Lucas Antônio Miranda Ferreira; et al. (2016)
Background: Despite recent advances in cancer therapy, the treatment of bone tumors remains a major challenge. A possible underlying hypothesis, limitation, and unmet need may be the inability of therapeutics to penetrate into dense bone mineral, which can lead to poor efficacy and high toxicity, due to drug uptake in healthy organs. The development of nanostructured formulations with high affinity for bone could be an interesting approach to overcome these challenges. Purpose: To develop a liposomal formulation with high affinity for hydroxyapatite and the ability to release doxorubicin (DOX) in an acidic environment for future application as a tool for treatment of bone metastases. Materials and methods: Liposomes were prepared by thin-film lipid hydration, followed by extrusion and the sulfate gradient-encapsulation method. Liposomes were characterized by average diameter, ζ-potential, encapsulation percentage, X-ray diffraction, and differential scanning calorimetry. Release studies in buffer (pH 7.4 or 5), plasma, and serum, as well as hydroxyapatite-affinity in vitro analysis were performed. Cytotoxicity was evaluated by MTT assay against the MDA-MB-231 cell line, and biodistribution was assessed in bone metastasis-bearing animals. Results: Liposomes presented suitable diameter (~170 nm), DOX encapsulation (~2 mg/mL), controlled release, and good plasma and serum stability. The existence of interactions between DOX and the lipid bilayer was proved through differential scanning calorimetry and small-angle X-ray scattering. DOX release was faster when the pH was in the range of a tumor than at physiological pH. The bone-targeted formulation showed a strong affinity for hydroxyapatite. The encapsulation of DOX did not interfere in its intrinsic cytotoxicity against the MDA-MB-231 cell line. Biodistribution studies demonstrated high affinity of this formulation for tumors and reduction of uptake in the heart. Conclusion: These results suggest that bone-targeted pH-sensitive liposomes containing DOX can be an interesting strategy for selectively delivering this drug into bone-tumor sites, increasing its activity, and reducing DOX-related toxicity. Keywords: hydroxyapatite-targeted formulations, bisphosphonates, pH-responsive nanostructures, bone-tumor treatment